Cortes cristalográficos em grafeno catalisado por nanopartículastermicamente ativadas - Luciana Vasconcelos Cambraia (2013)
In order to obtain graphene nanoribbons, the former technique catalytic hydrogenation of carbon was applied on graphene by using nanoparticles of nickel and platinum as catalysts. We investigated the qualitative behavior of the reaction in samples subjected to differentflows of hydrogen gas. For characterization of graphene and few layers graphene we provided tools such as Raman Spectroscopy, Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM). These analyzes revealed that there is a strong link between the amount of hydrogen gas and the complete hydrogenation reaction, showing thebest results for the greatest flow chosen. Thus, it was possible to better understand and optimize the etching mechanism by catalytic hydrogenation, resulting nanoribbons, constrictions and interesting geometric figures for in future works we can make electrical measurements of these materials and the fabrication of devices from them.